2020
DOI: 10.1111/ggi.13896
|View full text |Cite
|
Sign up to set email alerts
|

Promoting dementia‐friendly communities to improve the well‐being of individuals with and without dementia

Abstract: A community is the totality of human relationships, in which individuals live with and for others. This article discusses promoting dementia‐friendly community from the perspective of human relationships within a community. Improving the social well‐being of aging people is important; it is especially important for people with dementia, as dementia is a life‐changing syndrome that affects all aspects of one's life, including human relationships. Dementia‐friendly community requires support from the community i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 87 publications
(205 reference statements)
0
13
0
Order By: Relevance
“…Additionally, previous research has indicated that participation in time banking increases one's sense of community belonging, 21,32 and a sense of belonging and attachment to the community drives people to participate in further support activities for people with dementia 33,34 . Further, participation in such support activities per se has been shown to help prevent dementia due to mutually beneficial relationships within the community 35,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous research has indicated that participation in time banking increases one's sense of community belonging, 21,32 and a sense of belonging and attachment to the community drives people to participate in further support activities for people with dementia 33,34 . Further, participation in such support activities per se has been shown to help prevent dementia due to mutually beneficial relationships within the community 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research has indicated that participation in time banking increases one's sense of community belonging, 21,32 and a sense of belonging and attachment to the community drives people to participate in further support activities for people with dementia. 33,34 Further, participation in such support activities per se has been shown to help prevent dementia due to mutually beneficial relationships within the community. 35,36 Thus, time banking may lead to the creation of a virtuous cycle, in which respondents enhance their sense of community belonging, increase their motivation for participating in support activities, and help prevent dementia.…”
Section: Positive Effects Of Time Credits On Participation To Support Activities In Going Outmentioning
confidence: 99%
“…Globally, more than 43 million people are estimated to have dementia [ 1 ], the majority of whom live in the community [ 2 ]. A global action plan [ 3 ] calls for establishing dementia-friendly initiatives, which aim to change the attitudes and behaviors of the public, promote social inclusion, and help people with dementia engage in meaningful activity in the community [ 4 , 5 ]. Shopping is the most common outings for people with dementia [ 6 ], and 80% of them were reported to enjoy this activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While people with dementia rely on small neighborhood stores within walking distance to avoid complicated transportation and getting lost [ 8 ], they often have difficulty finding and paying for items in the store and may need help from store staff [ 8 , 9 ]. People with dementia and their informal caregivers want the stores’ staff to be trained in dementia, be helpful, and respond to emergencies [ 10 , 11 ], thus dementia training for store staff is integrated into the dementia-friendly initiatives [ 4 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dementia is rapidly increasing worldwide [1][2][3]. Since Japan is one of the most aging countries, its government has set the prevention of, and living well with, dementia as ultimate policy goals [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%